A kind of sulfurized polyacrylonitrile positive electrode material with high structural regularity and its preparation method and application
By pretreating polyacrylonitrile under aerobic conditions and optimizing its structure, the problems of cyclic stability and capacity attenuation of sulfur positive electrode materials in lithium sulfur batteries are solved, and a vulcanized polyacrylonitrile positive electrode material with high specific capacity and good cycle stability are achieved.
Patent Information
- Application Number
- CN202211630037.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-19
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2042-12-19
AI Technical Summary
The cyclic stability and capacity attenuation of sulfur cathode materials in lithium-sulfur batteries lead to low utilization of active substances and poor battery circulation performance.
By pretreating polyacrylonitrile under aerobic conditions, cyclization occurs, optimizing the main chain conjugated structure, increasing the pyridine structure content, and reducing the content of the five-membered ring of the defective structure, thereby improving the capacity and cycling stability of the battery.
A sulfur cathode material with a higher specific capacity has good cycle stability and rate performance, reducing the generation of polysulfides during charging and discharging.
Smart Images

Figure HDA0004005409410000011 
Figure HDA0004005409410000012
Abstract
Description
Technical Field
[0001] The present invention relates to the fields of electrochemistry and new energy, and in particular to a sulfurized polyacrylonitrile positive electrode material with high structural regularity, a preparation method of the sulfurized polyacrylonitrile positive electrode material with high structural regularity, a sulfurized polyacrylonitrile battery thereof, a preparation method of the sulfurized polyacrylonitrile battery, and applications of the same in organic batteries. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention and should not be regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] The development of clean energy vehicles and portable electronic devices has led to an increasing demand for batteries with long cycle life, high capacity, low self-discharge, and fast charge and discharge. Sulfur and lithium are both lightweight elements, with weight-to-capacity ratios of up to 1672mAh g-1 and 3860mAh g-1, respectively. Since the average voltage of lithium-sulfur batteries is 2.15V, their theoretical specific capacity and energy density are 2500Whkg-1 and 2800Wh L-1, respectively, which are much higher than traditional lithium-ion batteries. However, due to the "shuttle effect" caused by the polysulfides produced during the charge and discharge process of the traditional sublimated sulfur positive electrode active material, problems such as low utilization of active materials, rapid capacity decay, and poor battery cycle performance have been caused.
[0004] The problems existing in lithium-sulfur batteries are mainly concentrated on sulfur cathode materials. The modification of sulfur cathodes has always been a research focus, and many meaningful results have been achieved. According to the summary of research work in recent years, there are two main types of sulfur-based cathode materials: one is sulfur composite cathode materials, such as sulfur / porous carbon composite cathodes, sulfur / metal oxide composite cathodes, sulfur / metal sulfide composite cathodes, and sulfur / conductive polymer composite cathodes. The second is organic sulfur cathode materials. In the structure of this type of material, sulfur and polymer skeletons are connected together by covalent bonds, and their discharge process is completely different from the charge and discharge process of the cathode with sulfur as the active substance. Among these materials, sulfurized polyacrylonitrile materials have attracted widespread attention from researchers due to their excellent cycle stability and compatibility with ester electrolytes. However, with the development of new energy, higher requirements are also placed on the cycle stability of sulfurized polyacrylonitrile materials.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] Purpose of the Invention
[0007] The purpose of the present invention is to provide a sulfurized polyacrylonitrile positive electrode material with high structural regularity, a preparation method of the sulfurized polyacrylonitrile positive electrode material with high structural regularity, a sulfurized polyacrylonitrile battery thereof, a preparation method of the sulfurized polyacrylonitrile battery, and their application in organic batteries.
[0008] The present invention cyclizes polyacrylonitrile under aerobic conditions through pretreatment, optimizes the main chain conjugated structure of polyacrylonitrile, increases the content of pyridine structure, reduces the content of defective structure five-membered ring, and thus improves the capacity and cycle stability of the battery.
[0009] Solution
[0010] To achieve the purpose of the present invention, in a first aspect, the present invention provides a sulfurized polyacrylonitrile positive electrode material with high structural regularity, wherein D / I G The value is 1.10-1.20, and the pyridine structure content is 44-58%.
[0011] Furthermore, its D / I G The value is 1.10 to 1.19, optionally 1.115 to 1.17, optionally 1.12 to 1.168, optionally 1.127 to 1.168 (preferably 1.127 to 1.167), optionally 1.12 to 1.135, optionally 1.127;
[0012] And / or, the pyridine structure content is 44% to 56%, optionally 45% to 55%, optionally 45.71% to 54.34%, optionally 52% to 56%, optionally 54% to 55%, optionally 54.34%.
[0013] In a second aspect, a method for preparing a sulfurized polyacrylonitrile positive electrode material with high structural regularity is provided, including modification and sulfurization of polyacrylonitrile: wherein the modification method of polyacrylonitrile is: heat-treating polyacrylonitrile under aerobic conditions to prepare a cyclized polyacrylonitrile material.
[0014] The present invention uses pretreatment to cyclize polyacrylonitrile under aerobic conditions, optimizes the main chain conjugated structure of polyacrylonitrile, increases the content of pyridine structure, reduces the content of defective structure five-membered ring, thereby improving the capacity and cycle stability of the battery, and can obtain a sulfur positive electrode with a higher specific capacity. In addition, since almost no polysulfide is generated during the charge and discharge process, the battery has good cycle stability.
[0015] Furthermore, in the modification method of polyacrylonitrile,
[0016] The heat treatment includes: heating to 150-250°C for insulation reaction, optionally the insulation reaction temperature is 160-240°C, optionally 180-220°C, optionally 200-220°C, optionally 200°C; optionally, the insulation reaction time is 0.5-6h, optionally 1-5h, optionally 2-5h, optionally 1.8-2.5h, optionally 2h; preferably, the insulation reaction includes: 195-225°C (preferably 195-205°C) for reaction for 1.8-2.5h, and the insulation reaction of the heat treatment includes: insulation at 200°C for 2 hours, or insulation at 220°C for 2 hours, or insulation at 180°C for 2 hours.
[0017] Generally, when the holding temperature is high, the holding time can be shortened, and when the holding temperature is low, the holding time can be appropriately extended. For example, when the holding temperature is 160°C, the holding time can be 5 hours; when the holding temperature is 240°C, the holding time can be 1 hour; but too high a temperature may cause cross-linking between polyacrylonitrile chains, excessive loss of active hydrogen atoms, resulting in no substitution sites for sulfur atoms in the subsequent vulcanization process, very little sulfur content in the vulcanization product, or side reactions with oxygen leading to defects in the main chain structure.
[0018] Furthermore, the heating rate of the heat treatment to the insulation reaction is 1-5°C / min, optionally 1-3°C / min, optionally 2°C / min.
[0019] Furthermore, the aerobic condition is an air atmosphere.
[0020] Furthermore, the polyacrylonitrile is in powder form. Optionally, the polyacrylonitrile is ground before the heat treatment.
[0021] Furthermore, the vulcanization method is: mixing cyclized polyacrylonitrile with sublimated sulfur, adding alcohol and ball milling for several hours, drying after ball milling, and heating and vulcanizing in an inert gas to obtain a black powder.
[0022] Furthermore, the mass ratio of cyclized polyacrylonitrile to sublimated sulfur is 1:(3-6), optionally 1:4.
[0023] Furthermore, the drying condition is: drying in an oven at 50-70° C. for more than 6 hours.
[0024] Furthermore, the temperature of heating vulcanization is: heating from room temperature to 150-160° C. and keeping it for 1-3 hours, with a heating rate of 3-10° C. / min, continuing to heat to 250-500° C. and keeping it for 3-8 hours, and naturally cooling to room temperature.
[0025] Furthermore, the temperature of heating vulcanization is: heating from room temperature to 150-160°C at a heating rate of 3-10°C / min, keeping warm for 1-3 hours, then continuing to heat to 250-500°C at a heating rate of 3-10°C / min, keeping warm for 3-8 hours, and naturally cooling to room temperature.
[0026] Optionally, the temperature for heating vulcanization is: heating from room temperature to 150-160°C at a heating rate of 3-8°C / min, keeping warm for 1-3 hours, then continuing to heat to 250-350°C at a heating rate of 3-8°C / min, keeping warm for 3-8 hours, and naturally cooling to room temperature.
[0027] Furthermore, the temperature of the heating vulcanization is: heating from room temperature to 155°C at a heating rate of 5°C / min, keeping warm for 2 hours, then continuing to heat to 300°C at a heating rate of 5°C / min and keeping warm for 6 hours, and naturally cooling to room temperature.
[0028] Further, the desulfurization method is: the sulfurized black powder is heated from room temperature to 250-300°C in an inert gas at a heating rate of 3-10°C / min for more than 10 hours, the heating rate is 3-10°C / min, and naturally cooled to room temperature after the insulation process ends;
[0029] Furthermore, it also includes: desulfurization after sulfurization: heating the sulfurized black powder from room temperature to 300°C in an inert gas at a heating rate of 5°C / min and keeping it warm for more than 10 hours or 12 hours, and naturally cooling it to room temperature after the insulation process is completed.
[0030] In a third aspect, a sulfurized polyacrylonitrile battery is provided, comprising a positive electrode sheet, wherein the raw materials of the positive electrode sheet comprise: the sulfurized polyacrylonitrile positive electrode material with high structural regularity described in the first aspect or the sulfurized polyacrylonitrile positive electrode material with high structural regularity prepared by the preparation method described in the second aspect, and a conductive agent and a binder, wherein the mass ratio is 6:(2.5-3.5):(0.5-1.5).
[0031] Furthermore, the mass ratio of the highly structurally regular sulphurized polyacrylonitrile positive electrode material, the conductive agent and the binder is 6:3:1.
[0032] Furthermore, the conductive agent is acetylene black.
[0033] Further, the binder is a gelatin solution. Optionally, the concentration of the gelatin solution is 1.5-2.5 wt%. Optionally, the moisture in the binder is removed during the drying process of battery preparation.
[0034] In a fourth aspect, a method for preparing a sulfurized polyacrylonitrile battery is provided, wherein the sulfurized polyacrylonitrile positive electrode material with high structural regularity described in the first aspect or the sulfurized polyacrylonitrile positive electrode material with high structural regularity prepared by the preparation method described in the second aspect is mixed with a conductive agent and a binder to form a slurry, ball-milled to mix, coated, and dried to obtain a positive electrode sheet;
[0035] Furthermore, the conductive agent is acetylene black.
[0036] Furthermore, the binder is a gelatin solution, and optionally, the concentration of the gelatin solution is 1.5-2.5 wt %.
[0037] Furthermore, the ball milling time is 3 to 8 hours, optionally 5 hours.
[0038] Furthermore, the drying conditions after coating are: vacuum drying for 20 to 30 hours.
[0039] Further, the positive electrode sheet and the ether electrolyte are assembled into a battery; optionally, the ether electrolyte uses 0.1M lithium bistrifluoromethanesulfonyl imide (LiTFSI) dissolved in a solvent mixed with equal volumes of dioxolane (DOL) and ethylene glycol dimethyl ether (DME) (v:v=1:1).
[0040] In a fifth aspect, there is provided a use of the highly structurally regular sulfide polyacrylonitrile positive electrode material described in the first aspect, or the highly structurally regular sulfide polyacrylonitrile positive electrode material prepared by the preparation method described in the second aspect, or the sulfide polyacrylonitrile battery described in the third aspect, or the sulfide polyacrylonitrile battery prepared by the preparation method described in the fourth aspect in an organic battery.
[0041] Beneficial Effects
[0042] (1) The present invention cyclizes polyacrylonitrile under aerobic conditions by pretreatment, optimizes the main chain conjugated structure of polyacrylonitrile, increases the content of pyridine structure, and reduces the content of defective structure five-membered ring, thereby improving the capacity and cycle stability of the battery, and can obtain a sulfur positive electrode with a higher specific capacity. In addition, since almost no polysulfide is generated during the charge and discharge process, it has good cycle stability. The conjugated structure of the main chain of the sulfurized polyacrylonitrile, the positive electrode active material, can improve the stability and conductivity of the positive electrode, and can effectively alleviate the collapse of the positive electrode structure caused by the volume change during the charge and discharge process.
[0043] (2) The present invention optimizes the process of preparing vulcanized polyacrylonitrile by adding a desulfurization process after the vulcanization process. The obtained product is desulfurized. In this process, not only the excess sulfur that does not participate in the reaction is removed, but also the product that has undergone the vulcanization process reacts more fully.
[0044] (3) The polyacrylonitrile sulfide in the present invention is compatible with both ester electrolytes and ether electrolytes and has a wide range of applications. The polyacrylonitrile sulfide battery prepared by the present invention has a greatly improved specific capacity, high coulombic efficiency, low capacity attenuation rate, greatly improved cycle stability, and greatly improved rate performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] One or more embodiments are exemplarily described by the pictures in the accompanying drawings, and these exemplary descriptions do not constitute limitations on the embodiments. The special word "exemplary" here means "used as an example, embodiment or illustrative". Any embodiment described as "exemplary" here is not necessarily interpreted as being superior or better than other embodiments.
[0046] Figure 1 The figure is a comparison of the rate performance of ptSPAN and air200-SPAN in Comparative Example 1 and Example 1 of the present invention at different rates. Among them, air200-SPAN is the air200-SPAN battery prepared in Example 1, and ptSPAN is the ptSPAN battery prepared in Comparative Example 1.
[0047] Figure 2 The long cycle performance of ptSPAN and air200-SPAN in comparative example 1 and embodiment 1 of the present invention at a rate of 0.2C is compared. Among them, air200-SPAN is the air200-SPAN battery prepared in embodiment 1, and ptSPAN is the ptSPAN battery prepared in comparative example 1. DETAILED DESCRIPTION
[0048] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Unless otherwise expressly stated, throughout the specification and claims, the term "including" or its variations such as "comprising" or "including" will be understood to include the stated elements or components, without excluding other elements or other components.
[0049] In addition, in order to better illustrate the present invention, numerous specific details are provided in the specific embodiments below. It should be understood by those skilled in the art that the present invention can also be implemented without certain specific details. In some embodiments, raw materials, elements, methods, means, etc. well known to those skilled in the art are not described in detail, so as to highlight the main purpose of the present invention.
[0050] In the following examples, all raw materials are commercially available.
[0051] Electrochemical performance test of battery assembled with polyacrylonitrile sulfide cathode: rate performance was tested in the 1-3V voltage window at 0.2C, 1C, 2C, 3C and 5C (1C = 600mAg -1 ) rate for cycling; long cycle for charging and discharging at a rate of 0.2C in the 1-3V voltage window.
[0052] I D / I G Detection of the value: Raman spectroscopy was used for detection. The detection method was referred to Yang N, Shao R, Zhang Z, et al. Gelatin-derived carbon: carbonization mechanism and application in K-ionstorage[J]. Carbon, 2021, 178(13): 775-782.
[0053] Detection of pyridine structure content: XPS N1s spectrum detection was used. The detection method refers to Li Y, Zhou P, Li H, et al. A Freestanding Flexible Single-Atom Cobalt-Based Multifunctional Interlayer toward Reversible and Durable Lithium-Sulfur Batteries [J]. Small Methods, 2020, 4 (3): 1900701, and Razzaq AA, Yao Y, Shah R, et al. High-Performance Lithium Sulfur Batteries Enabled by a Synergy between Sulfur and Carbon Nanotubes [J]. Energy Storage Materials, 2018: 194-202.
[0054] Example 1
[0055] (1) Modification of polyacrylonitrile: Grind the polyacrylonitrile and then spread it evenly in a quartz tube. Then, open it and place it in a muffle furnace and heat it to 200°C at a heating rate of 2°C / min for 2 hours. Then, cool it naturally to room temperature. The resulting brown-yellow powder is the cyclized polyacrylonitrile material.
[0056] (2) Preparation of sulfided polyacrylonitrile: cyclized polyacrylonitrile and sublimed sulfur are mixed in a mass ratio of 1:5, and an appropriate amount of alcohol is added and ball-milled for several hours to mix evenly. After ball-milling, the mixture is placed in a 60°C oven for 12 hours to dry. The reactant powder is placed in a quartz tube, and then the quartz tube is placed in a hydrothermal reactor. After the hydrothermal reactor is sealed, it is heated from room temperature to 155°C at a heating rate of 5°C / min in an inert gas and kept warm for 2 hours. The heating rate is 5°C / min, and the heating rate is continued to be 5°C / min to 300°C and kept warm for 6 hours, and then cooled naturally to room temperature. After the black powder obtained in the sulfidation process is fully ground and evenly, the powder is placed in an open quartz tube, heated to 300°C at a heating rate of 5°C / min in an inert gas and kept warm for 12 hours, and then cooled naturally to room temperature. The obtained black powder is the sulfided polyacrylonitrile positive electrode material.
[0057] (3) Preparation of a battery assembled with a sulfurized polyacrylonitrile positive electrode: The positive electrode active material sulfurized polyacrylonitrile, the conductive agent acetylene black, and the binder gelatin solution (2wt%) were prepared into a slurry in a mass ratio of 6:3:1, ball-milled for 5 hours to mix evenly, and coated on the current collector aluminum foil with a scraper to a coating thickness of 200μm. After drying in a vacuum oven for 24 hours, it was cut into a positive electrode sheet with a diameter of 12mm; the Celgard2325 separator was cut into a disc with a diameter of 19mm; the negative electrode was a thick lithium sheet with a thickness of 2mm; an ether electrolyte was used, and 0.1M LiTFSI was dissolved in DOL:DME (v:v=1:1). The battery was assembled in an argon atmosphere in a glove box and sealed to make a sulfurized polyacrylonitrile battery.
[0058] The sulphurized polyacrylonitrile positive electrode material prepared in step (2) of Example 1 is recorded as "air200-SPAN" positive electrode material.
[0059] The battery prepared in step (3) of Example 1 is denoted as "air200-SPAN" battery.
[0060] Comparative Example 1
[0061] The difference from Example 1 is that the modification of step (1) is not performed, and steps (2) and (3) are directly performed. The prepared positive electrode material is recorded as "ptSPAN" positive electrode material, and the prepared battery is recorded as "ptSPAN" battery.
[0062] I of "air200-SPAN" positive electrode material and "ptSPAN" positive electrode material D / I G Value detection: I of the positive electrode material of "air200-SPAN" in Raman spectrum D / I GThe value is 1.127, which is lower than 1.210 of ptSPAN, which has a higher degree of graphitization, which may mean a higher content of six-membered rings, i.e., pyridine structures.
[0063] Detection of pyridine structure content of "air200-SPAN" positive electrode material and "ptSPAN" positive electrode material: In the N1s spectrum of XPS, the pyridine structure content of air200-SPAN is 54.34%, which is significantly higher than 49.01% of ptSPAN, indicating that the cyclization reaction of polyacrylonitrile (PAN) is beneficial to reducing the defective structure of the five-membered ring structure of the main chain of the SPAN material.
[0064] "air200-SPAN" battery, "ptSPAN" battery in the rate performance, such as Figure 1 , Figure 2 As shown in Figure 2, the specific capacity of air200-SPAN at high rates (1C, 2C, 3C and 5C) is significantly higher than that of ptSPAN, and the rate performance is improved. In the long cycle, the first discharge specific capacity of air200-SPAN is higher than 950 mAh g -1 The second cycle specific capacity is higher than 700mAh g -1 After 480 cycles, the specific capacity is still higher than 460 mAh g -1 The capacity decay rate per cycle is 0.07%; the first discharge specific capacity of ptSPAN is less than 930mAh g -1 The second cycle specific capacity is lower than 680 mAh g -1 , the specific capacity after 30 cycles is higher than 600mAh g -1 The capacity decay rate per cycle is 0.16%. When ptSPAN is cycled for 100 cycles, the specific capacity is less than 500 mAh g -1 , the capacity decay rate per cycle is as high as 2.84%.
[0065] This indicates that the sulfide polyacrylonitrile material prepared after modified pre-cyclization contains a high pyridine structure, the regularity of the main chain structure is improved, and the capacity retention rate is significantly improved.
[0066] Example 2
[0067] (1) Modification of polyacrylonitrile: Grind the polyacrylonitrile and then spread it evenly in a quartz tube. Then, open it and place it in a muffle furnace and heat it to 240°C at a heating rate of 2°C / min for 1 hour. Then, cool it naturally to room temperature. The resulting brown-yellow powder is the cyclized polyacrylonitrile material.
[0068] (2) Preparation of sulfided polyacrylonitrile: cyclized polyacrylonitrile and sublimed sulfur are mixed in a mass ratio of 1:4, and an appropriate amount of alcohol is added and ball-milled for several hours to mix evenly. After ball-milling, the mixture is placed in a 60°C oven for 12 hours to dry. The reactant powder is placed in a quartz tube, and then the quartz tube is placed in a hydrothermal reactor. After the hydrothermal reactor is sealed, it is heated from room temperature to 155°C at a heating rate of 5°C / min in an inert gas and kept warm for 3 hours, and then heated to 250°C at a heating rate of 5°C / min and kept warm for 6 hours, and then cooled naturally to room temperature. After the black powder obtained in the sulfidation process is fully ground and evenly, the powder is placed in an open quartz tube, heated to 300°C at a heating rate of 5°C / min in an inert gas and kept warm for 12 hours, and then cooled naturally to room temperature. The obtained black powder is the sulfided polyacrylonitrile positive electrode material.
[0069] (3) Preparation of a battery assembled with polyacrylonitrile sulfide: prepare a slurry of polyacrylonitrile sulfide, a conductive agent acetylene black, and a binder gelatin solution (1.5 wt%) in a mass ratio of 6:3:1, ball mill for 5 hours to mix evenly, apply it on the current collector aluminum foil with a scraper, and the coating thickness is 200 μm. After drying in a vacuum oven for 24 hours, cut it into a positive electrode sheet with a diameter of 12 mm; cut the Celgard2325 separator into a disc with a diameter of 19 mm; the negative electrode is a thick lithium sheet with a thickness of 2 mm; use an ether electrolyte, 0.1 M LiTFSI is dissolved in DOL:DME (v:v=1:1). The battery is assembled in an argon atmosphere in a glove box and sealed to make a polyacrylonitrile sulfide battery.
[0070] The positive electrode material prepared in step (2) of this embodiment D / I G The value is 1.202, and the pyridine structure content is 46.54%.
[0071] Example 3
[0072] (1) Modification of polyacrylonitrile: Grind the polyacrylonitrile and then spread it evenly in a quartz tube. Then, open it and place it in a muffle furnace and heat it to 220°C at a heating rate of 2°C / min for 2 hours. Then, cool it naturally to room temperature. The resulting brown-yellow powder is the cyclized polyacrylonitrile material.
[0073] (2) Preparation of sulfided polyacrylonitrile: cyclized polyacrylonitrile and sublimed sulfur are mixed in a mass ratio of 1:3, and an appropriate amount of alcohol is added and ball-milled for several hours to mix evenly. After ball-milling, the mixture is placed in a 60°C oven for 12 hours to dry. The reactant powder is placed in a quartz tube, and then the quartz tube is placed in a hydrothermal reactor. After the hydrothermal reactor is sealed, it is heated from room temperature to 155°C at a heating rate of 5°C / min in an inert gas and kept warm for 2 hours, and then heated to 300°C at a heating rate of 5°C / min and kept warm for 6 hours, and then cooled naturally to room temperature. After the black powder obtained in the sulfidation process is fully ground and evenly, the powder is placed in an open quartz tube, heated to 300°C at a heating rate of 5°C / min in an inert gas and kept warm for 12 hours, and then cooled naturally to room temperature. The obtained black powder is the sulfided polyacrylonitrile positive electrode material.
[0074] (3) Preparation of a battery assembled with polyacrylonitrile sulfide: prepare a slurry of polyacrylonitrile sulfide, a conductive agent acetylene black, and a binder gelatin solution (2 wt%) in a mass ratio of 6:3:1, ball mill for 5 hours to mix evenly, apply it on the current collector aluminum foil with a scraper, and the coating thickness is 200 μm. After drying in a vacuum oven for 24 hours, cut it into a positive electrode sheet with a diameter of 12 mm; cut the Celgard2325 separator into a disc with a diameter of 19 mm; the negative electrode is a thick lithium sheet with a thickness of 2 mm; use an ether electrolyte, 0.1 M LiTFSI is dissolved in DOL:DME (v:v=1:1). The battery is assembled in an argon atmosphere in a glove box and sealed to make a polyacrylonitrile sulfide battery.
[0075] The positive electrode material prepared in step (2) of this embodiment D / I G The value is 1.167, and the pyridine structure content is 45.71%.
[0076] In the long cycle performance test, the battery prepared in step (3) of this embodiment has a first cycle discharge capacity higher than 750 mAh g -1 The second cycle specific capacity is higher than 500mAh g -1 When the cycle reaches 30 times, the discharge capacity is still not less than 500mAh g -1 The capacity decay rate of each cycle is 0%, indicating good cycle stability.
[0077] Example 4
[0078] (1) Modification of polyacrylonitrile: Grind the polyacrylonitrile and then spread it evenly in a quartz tube. Then, open it and place it in a muffle furnace and heat it to 180°C at a heating rate of 2°C / min for 2 hours. Then, cool it naturally to room temperature. The resulting brown-yellow powder is the cyclized polyacrylonitrile material.
[0079] (2) Preparation of sulfided polyacrylonitrile: cyclized polyacrylonitrile and sublimed sulfur are mixed in a mass ratio of 1:5, and an appropriate amount of alcohol is added to the mixture for a few hours to mix evenly. After ball milling, the mixture is placed in a 60°C oven to dry for 12 hours. The reactant powder is placed in a quartz tube, and then the quartz tube is placed in a hydrothermal reactor. After the hydrothermal reactor is sealed, it is heated from room temperature to 155°C at a heating rate of 5°C / min in an inert gas and kept warm for 2 hours, and then heated to 300°C at a heating rate of 5°C / min and kept warm for 6 hours, and then cooled naturally to room temperature. After the black powder obtained in the sulfidation process is fully ground and evenly, the powder is placed in an open quartz tube, heated to 300°C at a heating rate of 5°C / min in an inert gas and kept warm for 12 hours, and then cooled naturally to room temperature. The obtained black powder is the sulfided polyacrylonitrile positive electrode material.
[0080] (3) Preparation of polyacrylonitrile sulfide positive electrode assembly battery: The positive electrode active material polyacrylonitrile sulfide, the conductive agent acetylene black, and the binder gelatin solution (2wt%) were prepared into a slurry in a mass ratio of 6:3:1, ball milled for 5 hours to mix evenly, and coated on the current collector aluminum foil with a scraper to a coating thickness of 200μm. After drying in a vacuum oven for 24 hours, it was cut into a positive electrode sheet with a diameter of 12mm; the Celgard2325 separator was cut into a disc with a diameter of 19mm; the negative electrode was a thick lithium sheet with a thickness of 2mm; an ether electrolyte was used, and 0.1M LiTFSI was dissolved in DOL:DME (v:v=1:1). The battery was assembled in an argon atmosphere in a glove box and sealed to make a polyacrylonitrile sulfide battery.
[0081] The positive electrode material prepared in step (2) of this embodiment D / I G The value is 1.168, and the pyridine structure content is 49.05%.
[0082] In the long cycle performance test, the battery prepared in step (3) of this embodiment has a first cycle discharge capacity higher than 900 mAhg -1 The second cycle specific capacity is higher than 650mAh g -1 When the cycle reaches 30, the discharge capacity is still 600 mAh g -1 The capacity decay rate per cycle is 0.13%, and the cycle stability is good.
[0083] Example 5
[0084] (1) Modification of polyacrylonitrile: Grind the polyacrylonitrile and then spread it evenly in a quartz tube. Then, open it and place it in a muffle furnace and heat it to 160°C at a heating rate of 2°C / min for 5 hours. Then, cool it naturally to room temperature. The resulting brown-yellow powder is the cyclized polyacrylonitrile material.
[0085] (2) Preparation of sulfided polyacrylonitrile: cyclized polyacrylonitrile and sublimed sulfur are mixed in a mass ratio of 1:5, and an appropriate amount of alcohol is added to the mixture for a few hours for uniform mixing. After the mixture is ball-milled, it is placed in a 60°C oven for drying for 12 hours. The reactant powder is placed in a quartz tube, and then the quartz tube is placed in a hydrothermal reactor. After the hydrothermal reactor is sealed, it is heated from room temperature to 155°C at a heating rate of 5°C / min in an inert gas and kept warm for 2 hours, and then heated to 500°C at a heating rate of 5°C / min for 4 hours, and then cooled naturally to room temperature. After the black powder obtained in the sulfidation process is fully ground and uniformly, the powder is placed in an open quartz tube, heated to 300°C at a heating rate of 5°C / min in an inert gas and kept warm for 12 hours, and then cooled naturally to room temperature. The obtained black powder is the sulfided polyacrylonitrile positive electrode material.
[0086] (3) Preparation of polyacrylonitrile sulfide positive electrode assembly battery: The positive electrode active material polyacrylonitrile sulfide, the conductive agent acetylene black, and the binder gelatin solution (2.5wt%) were prepared into a slurry according to a mass ratio of 6:3:1, ball milled for 5 hours to mix evenly, and coated on the current collector aluminum foil with a scraper to a coating thickness of 200μm. After drying in a vacuum oven for 24 hours, it was cut into a positive electrode sheet with a diameter of 12mm; the Celgard2325 separator was cut into a disc with a diameter of 19mm; the negative electrode was a thick lithium sheet with a thickness of 2mm; an ether electrolyte was used, and 0.1M LiTFSI was dissolved in DOL:DME (v:v=1:1). The battery was assembled in an argon atmosphere in a glove box and sealed to make a polyacrylonitrile sulfide battery.
[0087] The positive electrode material prepared in step (2) of this embodiment D / I G The value is 1.210, and the pyridine structure content is 43.53%.
[0088] In the long cycle performance test, the battery prepared in step (3) of this embodiment has a first cycle discharge capacity higher than 850 mAhg -1 The second cycle specific capacity is higher than 600mAh g -1 superior.
[0089] In summary, the present invention can make the graphitization degree of polyacrylonitrile higher (such as Example 1 relative to Comparative Example 1) by modifying polyacrylonitrile and heat treating it under aerobic conditions. D / I G The value of the embodiment 3 is reduced by 0.083), and the pyridine content is increased to a certain extent (for example, the pyridine content of the embodiment 1 is increased by about 5% relative to the comparative example 1), which is beneficial to improving the cycle stability. In addition, the attenuation rate of each cycle of the embodiment 3 (the attenuation rate of each cycle of the 30 cycles is 0%) and the attenuation rate of each cycle of the 30 cycles is 0.13%). D / I Gvalue and higher cycle stability.
[0090] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a sulfurized polyacrylonitrile positive electrode material with high structural regularity, characterized in that: Including modification and vulcanization of polyacrylonitrile, and desulfurization after vulcanization: The modification method of polyacrylonitrile is as follows: heat-treating polyacrylonitrile under aerobic conditions to prepare a cyclized polyacrylonitrile material; the heat treatment includes: heating to 200-220°C for heat preservation reaction, the heat preservation reaction time is 2-5 hours; the heating rate of the heat preservation reaction is 1-3°C / min; The vulcanization method is as follows: cyclized polyacrylonitrile and sublimed sulfur are mixed, alcohol is added and ball-milled for several hours, the ball-milled mixture is dried, and the mixture is heated and vulcanized in an inert gas to obtain a black powder; the mass ratio of cyclized polyacrylonitrile to sublimated sulfur is 1:5; the temperature for heating and vulcanization is as follows: heating from room temperature to 155°C at a heating rate of 5°C / min, keeping the temperature for 2 hours, and then continuing to heat to 300°C at a heating rate of 5°C / min and keeping the temperature for 6 hours, and naturally cooling to room temperature; Desulfurization after sulfurization includes: heating the sulfurized black powder in an inert gas from room temperature to 250-300°C at a heating rate of 3-10°C / min for more than 10 hours, and naturally cooling to room temperature after the heat preservation process is completed to obtain a sulfurized polyacrylonitrile positive electrode material; I of the sulfurized polyacrylonitrile positive electrode material prepared therefrom D / I G The value is 1.12~1.135, and its pyridine structure content is 52%~56%.
2. The preparation method according to claim 1, characterized in that: I of the sulfurized polyacrylonitrile positive electrode material prepared therefrom D / I G The value is 1.
127.
3. The preparation method according to claim 1, characterized in that: The pyridine structure content of the prepared sulfided polyacrylonitrile positive electrode material is 54%~55%.
4. The preparation method according to claim 1, characterized in that: The pyridine structure content of the prepared sulfided polyacrylonitrile positive electrode material is 54.34%.
5. The preparation method according to claim 1, characterized in that: In the modification method of polyacrylonitrile, the reaction temperature during the heat treatment is kept at 200°C.
6. The preparation method according to claim 1, characterized in that: In the modification method of polyacrylonitrile, the heat preservation reaction time is 1.8~2.5h.
7. The preparation method according to claim 1, characterized in that: In the modification method of polyacrylonitrile, the heat preservation reaction time is 2 hours.
8. The preparation method according to claim 1, characterized in that: In the modification method of polyacrylonitrile, the heat treatment and heat preservation reaction includes: heat preservation at 200°C for 2 hours.
9. The preparation method according to claim 1, characterized in that: In the modification method of polyacrylonitrile, the heating rate of the heat preservation reaction is 2°C / min.
10. The preparation method according to claim 1, characterized in that: The aerobic condition is an air atmosphere.
11. The preparation method according to claim 1, characterized in that: The polyacrylonitrile is in powder form.
12. The preparation method according to claim 1, characterized in that: The polyacrylonitrile was ground before the heat treatment.
13. The preparation method according to any one of claims 1 to 12, characterized in that: Drying conditions: drying in an oven at 50~70℃ for more than 6 hours.
14. The preparation method according to any one of claims 1 to 12, characterized in that: The desulfurization method is as follows: the sulfurized black powder is heated from room temperature to 300°C in an inert gas at a heating rate of 5°C / min and kept warm for more than 10 hours, and then naturally cooled to room temperature after the insulation process is completed.
15. The preparation method according to any one of claims 1 to 12, characterized in that: The desulfurization method is as follows: the sulfurized black powder is heated from room temperature to 300°C in an inert gas at a heating rate of 5°C / min and kept warm for 12 hours, and then naturally cooled to room temperature after the insulation process is completed.
16. The preparation method according to any one of claims 1 to 12, characterized in that: It includes: (1) Modification of polyacrylonitrile: Grind the polyacrylonitrile and then spread it evenly in a quartz tube. Then, place it in a muffle furnace with the tube open and heat it to 200°C at a heating rate of 2°C / min for 2 hours. Then, cool it naturally to room temperature. The resulting brown-yellow powder is the cyclized polyacrylonitrile material. (2) Preparation of sulfided polyacrylonitrile: cyclized polyacrylonitrile and sublimed sulfur are mixed in a mass ratio of 1:5, and an appropriate amount of alcohol is added and ball-milled for several hours to mix evenly. After ball-milling, the mixture is placed in a 60°C oven for drying for 12 hours. The reactant powder is placed in a quartz tube, and then the quartz tube is placed in a hydrothermal reactor. After the hydrothermal reactor is sealed, it is heated from room temperature to 155°C at a heating rate of 5°C / min in an inert gas and kept warm for 2 hours. The heating rate is 5°C / min, and the mixture is further heated to 300°C at a heating rate of 5°C / min and kept warm for 6 hours, and then naturally cooled to room temperature. After the black powder obtained in the sulfidation process is fully ground and evenly mixed, the powder is placed in an open quartz tube, heated to 300°C at a heating rate of 5°C / min in an inert gas and kept warm for 12 hours, and then naturally cooled to room temperature. The obtained black powder is the sulfided polyacrylonitrile positive electrode material.
17. A sulfurized polyacrylonitrile battery, characterized in that: The positive electrode sheet comprises raw materials of: a sulfide polyacrylonitrile positive electrode material with high structural regularity prepared by the preparation method described in any one of claims 1 to 16, and a conductive agent and a binder, with a mass ratio of 6: (2.5~3.5): (0.5~1.5).
18. The sulfurized polyacrylonitrile battery according to claim 17, characterized in that: The mass ratio of the highly structurally regular sulphurized polyacrylonitrile positive electrode material, the conductive agent and the binder is 6:3:
1.
19. The sulfurized polyacrylonitrile battery according to claim 17, characterized in that: The conductive agent is acetylene black.
20. The sulfurized polyacrylonitrile battery according to claim 17, characterized in that: The binder is a gelatin solution, and the moisture in the binder is removed during the drying process of battery preparation.
21. The sulfurized polyacrylonitrile battery according to claim 20, characterized in that: The concentration of the gelatin solution is 1.5~2.5wt%.
22. A method for preparing a sulfurized polyacrylonitrile battery, characterized in that: The sulfide polyacrylonitrile positive electrode material with high structural regularity prepared by the preparation method according to any one of claims 1 to 16 is mixed with a conductive agent and a binder to form a slurry, ball-milled and mixed, coated, and dried to obtain a positive electrode sheet.
23. The preparation method according to claim 22, characterized in that: The conductive agent is acetylene black.
24. The preparation method according to claim 22, characterized in that: The binder is a gelatin solution.
25. The preparation method according to claim 24, characterized in that: The concentration of the gelatin solution is 1.5~2.5wt%.
26. The preparation method according to claim 22, characterized in that: The ball milling time is 3~8h.
27. The preparation method according to claim 22, characterized in that: The ball milling time was 5 h.
28. The preparation method according to claim 22, characterized in that: The drying conditions after coating are: vacuum drying for 20 to 30 hours.
29. The preparation method according to claim 22, characterized in that: The positive electrode sheet and the ether electrolyte are assembled into a battery.
30. The preparation method according to claim 22, characterized in that: The ether electrolyte is prepared by dissolving 0.1 M lithium bis(trifluoromethanesulfonyl)imide in a solvent of equal volumes of dioxolane and ethylene glycol dimethyl ether.
31. Use of a sulfurized polyacrylonitrile positive electrode material with high structural regularity prepared by the preparation method according to any one of claims 1 to 16, or a sulfurized polyacrylonitrile battery according to any one of claims 17 to 21, or a sulfurized polyacrylonitrile battery prepared by the preparation method according to any one of claims 22 to 30 in an organic battery.
Citation Information
Patent Citations
Positive active material, preparation method thereof, positive pole piece prepared based on positive active material and preparation method thereof
CN110364720A
Polyacrylonitrile-sulphur composite material
US20140127589A1